Encyclopedia of education - Guthrie, James W. (New York : Macmillan Reference USA, 2003)
"The first edition, published in 1971, served for the past three decades as the most comprehensive reference source on education. The revised version proves a worthy successor. Its eight volumes contain over 850 articles written or reworked by more than 1,000 contributors. Nearly every article has been completely rewritten, with many new topics added. The six appendixes include information on achievement tests, state departments of education, legislation and court cases important to the field of education, and a 138-page index."--"The Top 20 Reference Titles of the Year," American Libraries, May 2004.
v. 1. AACSB-Commerce -- v. 2. Common-Expertise -- v. 3. Faculty-Hutchins -- v. 4. IEA-Lowenfeld -- v. 5. Macdonald-Putnam -- v. 6. Race-State -- v. 7. States-Zirbes -- v. 8. Appendixes. Index.
Includes bibliographical references and index.
Keywords: Education -- Encyclopedias